Young Students Social Interaction: Findings from a ‘Islamic Boarding Schools’ in Kudus, Central Java - Sa'adah, Kiswatus; Formen, Ali (BELIA: Early Childhood Education Papers, 2021)
This article discusses the social interactions of young santri that occur in Islamic boarding schools between young santri and older people as well as young santri and young santri, and manners in social interaction in Islamic boarding schools. Social interaction is a relationship between individuals or groups that respect and influence each other. Manners become the application and learning that is prioritized in Islamic boarding schools. Manners relate to polite behavior towards others. Islamic boarding schools instill good manners. The objectives of this study were (1) to find out the social interactions of young santri at the AL-Mabrur Kudus Islamic Boarding School (2) how the social interactions regarding the manners of young students in Al-Mabrur Islamic Boarding School. The research method used in this research is a case study with a descriptive qualitative approach. The results showed that the social interactions of young santri aged 6-8 years at the AL-Qudisyyah Islamic boarding school were carried out reciprocally. The language used in everyday interactions is using the Javanese Kromo language. The process of manners with social interaction is in the form of direct teaching from murobbi to students either during jokes or when learning. This article will present a discussion of all forms of social interaction that occur at the Al-Qudisyyah Islamic Boarding School, both between young students and fellow young students or even with older people.